2000
DOI: 10.1038/35020607
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations for proton translocation in the M state of wild-type bacteriorhodopsin

Abstract: The transport of protons across membranes is an important process in cellular bioenergetics. The light-driven proton pump bacteriorhodopsin is the best-characterized protein providing this function. Photon energy is absorbed by the chromophore retinal, covalently bound to Lys 216 via a protonated Schiff base. The light-induced all-trans to 13-cis isomerization of the retinal results in deprotonation of the Schiff base followed by alterations in protonatable groups within bacteriorhodopsin. The changed force fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
402
4
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(432 citation statements)
references
References 28 publications
23
402
4
1
Order By: Relevance
“…A series of intermediates designated J, K, L, M, N, and O are defined by spectroscopy, and M (M 410 ), which has an absorption peak at 410 nm and the longest lifetime, is only the intermediate containing a deprotonated Schiff base [134]. The light-induced conformational changes in bR in the frozen activated state of the wild type (WT) and bR mutants have been studied by x-ray crystallography and electron microscopy [137][138][139]. The extent of the changes reported varies depending on the methods used, but it is generally small (0.1−0.3 nm).…”
Section: Br In Response To Lightmentioning
confidence: 99%
“…A series of intermediates designated J, K, L, M, N, and O are defined by spectroscopy, and M (M 410 ), which has an absorption peak at 410 nm and the longest lifetime, is only the intermediate containing a deprotonated Schiff base [134]. The light-induced conformational changes in bR in the frozen activated state of the wild type (WT) and bR mutants have been studied by x-ray crystallography and electron microscopy [137][138][139]. The extent of the changes reported varies depending on the methods used, but it is generally small (0.1−0.3 nm).…”
Section: Br In Response To Lightmentioning
confidence: 99%
“…Under the native condition, bR forms trimers that assemble into a two-dimensional hexagonal lattice called the purple membrane (PM) (Blaurock, 1971). Previously, numerous structural studies of bR in PM were performed under unphotolyzed (Sass et al, 2000) or frozen activated (Luecke et al, 1999;Subramaniam and Henderson, 2000;Vonck, 2000, Lanyi andSchobert, 2003;Hirai and Subramaniam, 2009) states. Recently, by means of high-speed atomic force microscopy (HS-AFM) (Ando et al, 2001;Ando et al, 2008), light-induced conformational changes of bR have been visualized in real-time and real-space (Shibata et al, 2010;Shibata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the photocycle, a series of spectral intermediates, designated J, K, L, M, N, and O, occur in that order 12 . The light-induced conformational changes in bR have been investigated by various methods 15-25 , leading to a consensus that the proton channel at the cytoplasmic surface is opened by the tilting of helix F away from the protein center 21,23,24 . Sass et al reported helix F displacement of ~0.1 nm in the late M state, based on X-ray diffraction of the three-dimensional crystal of wild type (WT) 21 .…”
mentioning
confidence: 99%
“…The light-induced conformational changes in bR have been investigated by various methods [15][16][17][18][19][20][21][22][23][24][25] , leading to a consensus that the proton channel at the cytoplasmic surface is opened by the tilting of helix F away from the protein center 21,23,24 . Sass et al reported helix F displacement of ~0.1 nm in the late M state, based on X-ray diffraction of the three-dimensional crystal of wild type (WT) 21 . However, a larger structural change in bR was reported in 3 the electron crystallography study of the D96G, F171C, F219L triple mutant of bR: displacement of helix F by ~0.35 nm away from the center of the protein 23 .…”
mentioning
confidence: 99%